Sistem Absensi Face Recognition Multi-Platform Terintegrasi Untuk Manajemen Kehadiran Pengguna - Achsel Aldrian (Sekolah Tinggi Manajemen Informatika dan Komputer (STIMIK) Bina Mulia Palu, 2026)
The adoption of digital attendance systems has considerably improved the management and recording of employee attendance, replacing traditional manual procedures that are vulnerable to human error and potential data manipulation. Nevertheless, operational issues may occur when attendance devices malfunction or become unavailable, resulting in inaccurate attendance data. This research seeks to design and implement an automated attendance system based on Multi-Platform Face Recognition technology to improve the precision of employee verification. Additionally, the system integrates GPS-based location validation to ensure that attendance activities are performed only within authorized geographic boundaries. The development process follows the System Development Life Cycle (SDLC) framework using the Waterfall model, which includes the phases of planning, requirements analysis, system design, implementation, and testing. To assess system performance and functionality, Black Box Testing is employed to ensure that all features function properly and meet the predefined system requirements.